Flooding in ephemeral streams: incorporating transmission losses. Issue 2 (30th November 2017) - Pacheco-Guerrero, A.; Goodrich, D. C.; González-Trinidad, J.; Júnez-Ferreira, H. E.; Bautista-Capetillo, C. F.
ABSTRACT: Streamflow in semi-arid lands commonly occurs in the form of flash floods in dry-bed ephemeral streams. The goal of this research was to couple hydrological and 2D hydraulic model treatments of channel transmission losses, in order to show the impact of not taking transmission losses on flood hazard mapping into consideration. For hydraulic modeling the reach that is located between flumes 2 and 1 in the Walnut Gulch Experimental Watershed was tested. Two hydraulics models were set up, the first does not incorporate channel transmission and the second was developed to take into account several hydrographs with transmission losses as boundary conditions. The error in volume and peak runoff rate between the observed and simulated data ranges was in the order of –4.5–34.4% for runoff volume and –16.4–9.6% for peak runoff rate. The computation output interval time in the hydraulic model was 60 s and the duration of flood inundation was 6.67 h. There are important differences in depth between the two flood maps, with 0.68 maximum and 0 m minimum. The importance of using models with the dynamic treatment of transmission losses is the ability to provide an improved estimate for flood hazard mapping.